Co-designing a Canadian adaptation of a lifestyle-oriented intervention aimed to improve daily functioning of individuals living with chronic pain: a multi-method study protocol of REVEAL(OT) Canada - Masse, J.; Nielsen, S. S.; Christensen, J. R.; Skou, S. T.; Côté, J.; Saunders, S.; Lagueux, É.; Boulanger, A.; Perez-Martinez, J.; Lussier, M.; Pagé, M. G. (Frontiers in Rehabilitation Sciences, 2023)
Background: Living with chronic pain (CP) often implies major lifestyle changes, including modifications of daily routines and work. Surprisingly, few validated and effective interventions specifically target functional outcomes in this population. Redesign your Everyday Activities and Lifestyle with Occupational Therapy (REVEAL(OT)) is a lifestyle-oriented intervention led by occupational therapists that directly targets the daily functional challenges of living with CP. The intervention was initially developed and studied as an add-on to standard treatment delivered by Danish multidisciplinary specialized pain clinics. Adapting, implementing, and evaluating REVEAL(OT) within the Canadian healthcare system will contribute to broadening the scope of treatments offered in specialized pain clinics that do not yet include occupational therapy. Objective: The proposed study aims to define and refine REVEAL(OT)/CA with partners (authors of original intervention, people with lived experience, clinicians, managers). Methods: This participatory action research will use a multi-method design and follow the ORBIT model for developing behavioral treatments for chronic diseases. A process of co-construction with partners and an advisory committee will take place in two Montreal specialized pain clinics. It consists of two related work packages (WPs). In WP1, a first series of focus groups with partners (n=86) and workshops with the advisory committee will be conducted to co-develop the hypothetical pathway describing intervention components and their potential mechanisms of action on targeted outcomes, as well as the first version of the adapted intervention manual. WP2 will co-refine REVEAL(OT)/CA by exploring its acceptability, feasibility and mechanisms of action through intervention deliveries (at least twice in each of two specialized pain clinics; n≥60 patients) and focus groups and/or individual interviews with participating patients and partners. At the end of this study, the intervention manual will be generated both in French and English. Discussion: This study will set the stage for subsequent implementation and effectiveness assessment projects and be an important step towards the deployment of interventions aiming to improve engagement in meaningful daily activities among adults living with CP.